Use of bio-lac fusion strains to study regulation of biotin biosynthesis in Escherichia coli. - Barker, D F (1980)
The technique developed by Casadaban (M. J. Casadaban, J. Mol. Biol. 104: 541-555, 1976) has been employed to construct Escherichia coli K-12 derivatives in which the genes determining lactose utilization are fused to the regulatory region of the biotin operon. Fusions of the lac genes to either arm of this divergently transcribed operon have been isolated. When the operon is derepressed, expression of the lac genes is sufficient to permit growth on lactose minimal medium. Repressing conditions prevent growth on lactose. This property of bio-lac fusion strains, as well as the ease of determining the level of operon expression by assaying beta-galactosidase, was used for the isolation and characterization of mutants defective in repression. Preliminary analyses of several newly isolated regulatory mutants are presented. For the several birA mutants examined, there appeared to be no direct correlation between effects on minimum biotin requirement and alterations in repressibility, suggesting a possible dual function for the gene. Parallel attempts to obtain fusions of lac to bioH were unsuccessful, indicating lack of direct biotin control at the bioH locus.